Study the Concentration of Naturally Occurring Radioactive Materials in the Samples of Rice and Salt in Baghdad Governorate - Hameed, Ban S; Rejah, Basim K; Muter, Sara S (Al-Nahrain Journal of Science, 2018)
In this study, specific activities of naturally occurring radioactive materials were measured in selected samples of rice and salt available in local markets in Baghdad and then calculate hazard indices as well as the concentration of radioactive iodine in these samples using the detector system sodium iodide enhanced by thallium NaI(Tl). This study showed that the average quality of the specific activities of uranium 238 was 5.55 Bq / kg, thorium 232 was 5.6 Bq / kg and potassium 40 was 621 Bq / kg, while the content of iodine was 131 2.6 Bq / kg.Measurements of hazard indices show that the concentrations of these isotopes in all samples are within the allowable limits internationally except Al-Nasoor sample which was the total of Hinternal and Hexternal indices more than one. All data were measured at the January of 2015.